An exploration of trunk reposition error in subjects with acute stroke: An observational design. Issue 3 (2nd April 2016) - Learman, Kenneth E.; Benedict, James A.; Ellis, Alyson R.; Neal, Ashley R.; Wright, Jacob A.; Landgraff, Nancy C.
Abstract : Background & Objective: Trunk reposition error (TRE) is a component of trunk control, yet has not been reported in acute stroke. The purpose of this study was to quantify TRE in acute stroke and report this with related rehabilitation outcomes. Methods: Sixty subjects, 30 with acute stroke and 30 healthy controls, completed this study. Subjects with acute stroke were measured before and after an in-patient acute rehabilitation stay. Measures: TRE using an electromagnetic tracking device, Berg Balance Scale, Postural Assessment Scale for Stroke, and Functional Independence Measures. Pre-post measures were analyzed with paired t -tests. Between-group measures were analyzed with independent w -tests. Results: There were significant between group differences (acute stroke vs. controls) for all functional outcome measures ( P < 0.001) and for three-dimensional TRE ( P = 0.001). There were significant improvements in all functional outcome measures following an in-patient rehabilitation stay ( P < 0.001). All measures of TRE reduced but did not achieve significance. Conclusion: TRE was not as severely impaired as anticipated and was variable based on plane of measure. Time in a rehabilitation setting produced significant improvements in functional outcomes but TRE improvements were not as robust. These results indicate a need for further investigation of the strength of the interrelationship between TRE and function.